Implementation of the First Principle of Pancasila in the Context of Character Education in Madrasas or Islamic Educational Institutions - Salni, Salni (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This research aims to examine the manifestation of the first principle of Pancasila, Belief in One Supreme God, in the social interactions of madrasah students and to explore the effectiveness of artificial intelligence (AI)-assisted learning media in supporting values education. The issues raised are students’ low applicative understanding of Divine values in a social context and the limitations of conventional media in forming tolerant attitudes. This research uses a qualitative approach with data collection techniques including observation, interviews, and documentation of elementary school students in the Kendari region. Data analysis was performed using NVivo 14 software to systematically extract key themes. The results show that AI-based learning media significantly helps students understand Divine values contextually and communicate them through tolerant social interactions, both verbally and nonverbally. The use of this technology also impacts the improvement of creativity, self-reflection, and quality of student learning. This research provides a conceptual contribution to technology-based character education and offers an innovative pedagogical approach for Islamic educational institutions in the digital era.